Czynnik ludzki w podejściu procesowym do zarządzania w świetle badań służb zaopatrzenia przedsiębiorstw przemysłowych - Jokiel, Grzegorz (The meaning of human factor in process management in the light of supply services survey, 2006)
The article focuses on human factor significance in process approach implementation for management. The article presents results of empirical research carried out with management of purchasing department in 34 industrial enterprises. The main thesis of abstract is underestimating soft factors of management (culture organizational, know how, atmosphere of work), relatively to hard factors (structure, processes, procedures) during implementation of process approach in enterprises. This opinion is supported by results of research, which indicate in sphere of management Staff worrying phenomenon, like: apparent advantage of negative motivation stimulilimited investments in employees’ skills and knowledge development, sustaining stiff functional divisions, lack of cooperation between the departments or units in the enterprise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 198-210